Enabling interactive augmented prototyping by a portable hardware and a plug-in-based software architecture - Verlinden, Jouke (Strojniški vestnik, 2008)
Interactive Augmented Prototyping (IAP) combines digital and physical modelingmeans to support design processes. Although pilot implementations indicate a possible added value, practical use is hindered by the fact that no off-the-shelf solution exists.. Based on empirical studies and assessment of emerging technologies, this article introduces a projector-based IAP hardware platform called I/O Pad. Furthermore, a flexible software architecture is presented that supports a multitude of input devices and usage scenarios. In this architecture, an existing 3D CAD system is extended bya collection of plug-ins. The plug-ins are responsible for managing specific elements of the interactive augmented prototyping process. A first implementation has been developed, using a small projector and a handheld PC, which proves the wireless versatility of the hardware platform. The proposed software architecture allows the designer to work in a familiar modeling environment yet includes powerful concepts from tangible user interfaces to support several types of interaction with physical components.
Keywords: prototipi; načrtovanje; računalniška arhitektura